Kandungan Gizi dan Aktivitas Antioksidan Permen Jelly Buah Pedada (Sonneratia Caseolaris) dengan Penambahan Karagenan - Dini Wulan Dari; Dwi Tria Ramadani; Aisah Aisah (Jurnal Akademika Baiturrahim Jambi, 2020)
Pedada fruit (Sonneratia caseolaris) is one of the mangrove varieties that has a high nutritional content and has the potential as an antioxidant. In general, pedada is still underutilized by the community because it tastes sour and feels tight when consumed directly. One of the efforts in utilizing the pedada fruit is processing it into jelly candy. The purpose of this study was to determine the chemical characteristics of pedada jelly candy with the addition of carrageenan. This research is an experimental design using a quantitative descriptive approach with P2K2(100 ml  of pedada fruit juice and 20 gr carrageenan) and P0K2 contol samples (without pedada fruit juice and 20 gr of carrageenan). To find out the chemical characteristics were tested Carbohydrate, protein, fat, fiber, water content, ash content, vitamin C and Antioxidant activity. This research was conducted in May-August 2018. Jelly candy making was carried out at the STIKes Baiturrahim Jambi Nutrition and Food Laboratory, Chemical characteristics were tested by proximate analysis (Carbohydrate, protein, fat, fiber, water content, ash content), iodimetry (vitamin c) method and DPPH (Antioxidant activity) method. The best treatment in making Pedada jelly candy which is very preferred, namely P2K2 (100 ml pedada fruit juice and 20 gr carrageenan) with a carbohydrates (69.83%), protein (5.66%), fat (9.89%), water content (39.26%), ash content (9.67%), fiber (0.67%), vitamin C (14.08%) and antioxidant activity (67.34%).